(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2019)
Working the Margins of Community-Based Adult Learning is a well-rounded example of how art and creative forms of expression can influence, aid, and elevate transformative learning in community-based adult education. Specifically, the authors Shauna Butterwick and Carole Roy use an edited book format in a cohesive way to “gather stories from the margins and explore how various art and creative forms of expression can enable the voices of underrepresented individuals and communities to take shape and form” (p. ix).